Delivering climate resilient and productive sires to improve livelihoods of farmer communities at scale - Haile, Aynalem; Getachew, Tesfaye; Mueller, Jack; Santos, Bruno; Rekik, Mourad; Belay, Berhanu; Gizaw, Solomon; Rischkowsky, Barbara (International Center for Agricultural Research in the Dry Areas, 2023)
Delivering climate resilient and productive sires to improve livelihoods of farmer communities at scale.